2016
DOI: 10.12705/652.5
|View full text |Cite
|
Sign up to set email alerts
|

Generic recircumscription in the Loxocarpinae (Gesneriaceae), as inferred by phylogenetic and morphological data

Abstract: The Loxocarpinae, also known as the “Boea group”, are the subtribe of Gesneriaceae which includes Boea and a number of segregated genera and close relatives. This group currently comprises over 200 species in 15 genera. Here we present the most up‐to‐date phylogeny, covering all the genera known to belong to the group, based on Bayesian inference and parsimony of the nuclear ITS and the plastid regions trnL‐trnF (intron and spacer) and ndhF‐trnLUAG (spacers). The results show discrepancies between the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 27 publications
2
35
0
Order By: Relevance
“…Many of the sequences used were published in our previous studies (Möller et al 2011a, Middleton and Möller 2012, Middleton et al 2015, Puglisi et al 2016, with the addition of newly generated data for 12 taxa, including the unknown plant from Thong Pha Phum, Poopath, Sae Wai, Kheiwbang and Jirakon 1370. A few remaining sequences were downloaded from GenBank.…”
Section: Methodsmentioning
confidence: 99%
“…Many of the sequences used were published in our previous studies (Möller et al 2011a, Middleton and Möller 2012, Middleton et al 2015, Puglisi et al 2016, with the addition of newly generated data for 12 taxa, including the unknown plant from Thong Pha Phum, Poopath, Sae Wai, Kheiwbang and Jirakon 1370. A few remaining sequences were downloaded from GenBank.…”
Section: Methodsmentioning
confidence: 99%
“…The genus was segregated from Paraboea (C.B.Clarke) Ridl. by Puglisi et al (2016) as a result of a study of the Loxocarpinae which showed that the species now in Middletonia did not form a monophyletic group with the rest of Paraboea. The segregation from Paraboea is supported by both molecular data and the morphological characters discussed below.…”
Section: Introductionmentioning
confidence: 99%
“…Generic delimitation in Asian Gesneriaceae has been the focus of much recent research and has led to considerable change (Wei et al, 2010;Möller et al, 2011Möller et al, , 2014Möller et al, , 2016Puglisi et al, 2011Puglisi et al, , 2016Wang et al, 2011;Weber et al, 2011aWeber et al, , 2011bMiddleton & Möller, 2012;Middleton et al, 2014. This research, much of it based on the results of DNA sequence data, has resulted in an overall reduction in the number of genera but also the description of new genera to accommodate new species which were found to belong to previously unknown lineages , and the splitting up of genera found to be polyphyletic (Weber et al 2011a;Möller et al, 2014).…”
Section: Introductionmentioning
confidence: 99%